1999
DOI: 10.1074/jbc.274.3.1240
|View full text |Cite
|
Sign up to set email alerts
|

A Requirement for Phosphatidylinositol 3-Kinase in Pseudopod Extension

Abstract: Phagocytosis requires actin assembly and pseudopod extension, two cellular events that coincide spatially and temporally. The signal transduction events underlying both processes may be distinct. We tested whether phagocytic signaling resembles that of growth factor receptors, which induce actin polymerization via activation of phosphatidylinositol 3-kinase (PI 3-kinase). Fc␥ receptor-mediated phagocytosis was accompanied by a rapid increase in the accumulation of phosphatidylinositol 3,4,5-trisphosphate in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
398
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(444 citation statements)
references
References 74 publications
37
398
1
8
Order By: Relevance
“…The precise role of the proposed syk-PI3-kinase-racgelsolin cascade remains to be proven. However, syk, PI3-kinase, and rac are needed to complete phagocytosis (24,25,36,39,40). Rac appears to be specific for IgG-mediated phagocytosis and rho for complement-mediated phagocytosis (36), although a role for rho in Fc␥R-mediated phagocytosis has also been reported (41).…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of the proposed syk-PI3-kinase-racgelsolin cascade remains to be proven. However, syk, PI3-kinase, and rac are needed to complete phagocytosis (24,25,36,39,40). Rac appears to be specific for IgG-mediated phagocytosis and rho for complement-mediated phagocytosis (36), although a role for rho in Fc␥R-mediated phagocytosis has also been reported (41).…”
Section: Discussionmentioning
confidence: 99%
“…PIP3 is rapidly accumulated in phagocytic cups after ligation of FcγRs in macrophages (Cox et al, 1999;Marshall et al, 2001). Moreover, inhibition of PI3K activity blocks pseudopod extension and phgocytosis without affecting actin polymerization (Cox et al, 1999).…”
Section: Em Brane M Obilization During Phagocytosismentioning
confidence: 99%
“…However, it is not clear how the signal pathway is coupled between FcγR and the activation of Cdc42 and Rac1. PI3K is also involved in pseudopod extension (Cox et al, 1999) and myosin X is able to couple actin polymerization and pseudopod extension (Cox et al, 2002). (B) CR3-mediated phagocytosis.…”
Section: S Uperoxide Form Ation Through N a D P H Oxidase Nadph Oxidamentioning
confidence: 99%
“…Although some evidence shows that engagement of TLR2 or TLR4 can activate the PI3K/Akt pathway and increase TNF production [15,16], other work has indicated that PI3K/Akt activation negatively regulates TLR signaling in macrophages while positively regulating FccR signaling required for phagocytosis. Inhibition of PI3K in macrophages enhances LPS-induced activation of Erk, Jnk, p38 and NF-jB, increases LPS-induced induction of TNF and IL-6, stimulates inducible nitric oxide synthase (iNOS) expression and nitric oxide (NO) synthesis, and reduces the survival of endotoxemic mice [17][18][19][20][21][22][23][24][25]. These disparate observations may reflect cell type-or ligand-specific differences in the role of PI3K in macrophage/monocytes and DC, which are cell types that have yet to be fully explored in the Leishmania context [26].…”
Section: Introductionmentioning
confidence: 99%